Master class with Philippe Jaroussky Académie Musicale Philippe Jaroussky - Chabrier, Emmanuel 1841-1894; Handel, George Frideric 1685-1759; Massenet, Jules 1842-1912; Handel, George Frideric 1685-1759; Poulenc, Francis 1899-1963; Mozart, Wolfgang Amadeus 1756-1791; Fauré, Gabriel 1845-1924; Liszt, Franz 1811-1886; Handel, George Frideric 1685-1759; Donizetti, Gaetano 1797-1848; Handel, George Frideric 1685-1759 (DakApp, 2017)
The celebrated countertenor Philippe Jaroussky gives a voice master class to students of the "Mozart" class, the first year of the Académie Musicale Philippe Jaroussky, which opened its doors last September at La Seine Musicale. Singing gave me a real chance to fulfill my potential in my adult life. Today, after a career already spanning 20 years, I feel a great need to give others the same chance that I was given, transmitting my passion and offering young people without access to this universe the opportunity to encounter classical music through an intensive and innovative training program. - Philippe Jaroussky Pianists, violinists, cellists, and singers... follow the 27 young talents of the Académie Musicale Philippe Jaroussky in their illuminating work with David Kadouch (piano), Geneviève Laurenceau (piano), Christian-Pierre La Marca (cello), and Philippe Jaroussky (voice)
Keywords: Chansons; Voice; Voice -- Instruction and study; Songs -- Excerpts, Arranged; masterclass; Webcast; excerpts; Songs; Instructional films; Feature films; Excerpts; Arrangements (Music); Internet videos; Extraits; Arrangements (Musique); Films de formation; Vidéos sur Internet